PTEN is recognized as a prognostic-related biomarker and inhibits proliferation and invasiveness of skull base chordoma cells - Tian, Kaibing; Ma, Junpeng; Wang, Ke; Li, Da; Zhang, Junting; Wang, Liang; Wu, Zhen (Frontiers in Surgery, 2022)
Objective. This work aimed to examine the function of phosphatase and tensin homologue deleted on chromosome 10 (PTEN) in skull base chordoma (SBC) at the clinical and cellular levels. Methods. Totally 65 paraffin-embedded and 86 frozen specimens from 96 patients administered surgery were analyzed. Immunohistochemical staining and quantitative real-time polymerase chain reaction were performed, and the associations of PTEN expression with clinical features were assessed. At the cellular level, PTEN was knocked down by the siRNA approach in the UCH-1 cell line, and cell proliferation and invasion were detected by the CCK-8 and migration assays, respectively. Results. At the protein level, PTEN expression was increased in non-bone-invasive tumor samples in comparison with bone-invasive specimens (p=0.025), and elevated in soft SBCs in comparison with hard tumors (p=0.017). Increased PTEN protein expression was associated with decreased risk of tumor progression (p=0.002; hazard ratio =0.981, 95% confidence interval: 0.969-0.993). At the gene expression level, the cut-off value was set at 10.5 after ROC curve analysis, and SBC specimens were divided into two groups: PTEN high group, ∆Ct value below 10.5; PTEN low group, ∆Ct value above 10.5. In multivariate regression analysis of PFS, the risk of tumor progression was increased in PTEN low group tumors in comparison with PTEN high group SBCs (p=0.006). In the CCK-8 assay, in comparison with control cells, PTEN knockdown cells had increased absorbance, suggesting elevated cell proliferation rate. In the invasion assay, the number of tumor cells penetrating into the lower chamber was significantly increased in the PTEN knockdown group compared with control cells. Conclusions. Decreased PTEN expression in SBC, at the protein and gene levels, is associated with reduced PFS. PTEN knockdown in chordoma cells led to enhanced proliferation and invasiveness.